DEVELOPMENT OF E-MODULES BASED ON BLOG INSTRUCTIONAL DESIGN COURSES OF LAMONGAN ISLAMIC UNIVERSITY - Sugiarni; M. Subandowo; Hari Karyono (Institute of Computer Science (IOCS), 2022)
The purpose of this development is to produce a Blog-Based E-Module on Instructional Design Courses at private universities in Lamongan in particular and it is also expected for students as a whole, because Blog-Based E-Modules are generally opened access via an internet connection. The development model used in the development of interactive learning multimedia is the ADDIE model. The development stages of the ADDIE model consist of five stages which include analysis, design, development, implementation and evaluation. The result of this development is that this Blog-Based E-Module Product has a material feasibility level of 86.66%, a learning design feasibility 94.28%, and a learning media feasibility 94.28%. While the small group trial rate is 90.79% and based on field trials 91.22% with very decent qualifications and does not need to be revised.